2024
DOI: 10.1002/ejsc.12063
|View full text |Cite
|
Sign up to set email alerts
|

How are elite tennis matches won at Wimbledon? A comparison of close and one‐sided contests

Anna Fitzpatrick,
Joseph A. Stone,
Simon Choppin
et al.

Abstract: Notational analysis investigations of several sports have suggested that the performance characteristics associated with success differ by match closeness. It is not known whether this is the case in tennis. Therefore, this study aimed to first develop operational definitions for closely contested and one‐sided tennis matches, then establish whether the important performance characteristics in elite grass court tennis differ by match closeness. Data from 365 men and 374 women's Wimbledon single matches played … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Findings revealed that points of 0-4 shot rally length (i.e., short points) was the most important performance characteristic in terms of winning matches at Wimbledon, irrespective of sex (male/ female), time (from 1992 to 2017) and match closeness (closely contested/one-sided) (Fitzpatrick et al, 2024). Coaches should be aware of the prevalence and importance of short points, and design players' training accordingly.…”
Section: Implications For Coachesmentioning
confidence: 98%
See 1 more Smart Citation
“…Findings revealed that points of 0-4 shot rally length (i.e., short points) was the most important performance characteristic in terms of winning matches at Wimbledon, irrespective of sex (male/ female), time (from 1992 to 2017) and match closeness (closely contested/one-sided) (Fitzpatrick et al, 2024). Coaches should be aware of the prevalence and importance of short points, and design players' training accordingly.…”
Section: Implications For Coachesmentioning
confidence: 98%
“…Longitudinal analysis of men's and women's matches at Wimbledon showed that although the characteristics of matchplay evolved between 1992 and 2017, short points (points of between 0 and 4 shots) remained the most important aspect throughout. Informed by coaches' knowledge of the sport, we then defined 'closely contested' and 'one-sided' tennis matches, with analysis revealing that short points remain highly important in both closely contested and one-sided matches (Fitzpatrick et al, 2024). With only 3 weeks typically separating Roland Garros and Wimbledon, a comparison of the two Grand Slams provided important context to inform players' training strategies during the crucial, but timepressured, clay-to-grass surface transition (Fitzpatrick et al, 2019).…”
Section: Key Findingsmentioning
confidence: 99%